(untitled) (Journal of Sustainable Engineering & Renewable Energy, 2025)
Coconut dehusking is a labour-intensive process, necessitating efficient mechanized solutions to enhance productivity and reduce physical strain, this study aimed to optimize a coconut dehusking machine using Design Expert v13.0, a labour-intensive process. A CAD-based model was developed and simulated, and mathematical models were derived using dimensional analysis. The I-Optimal custom design of Response Surface Methodology (RSM) was validated through 22 experimental runs. The results showed strong agreement between the experimental and predicted dehusking efficiencies. The machine achieved a maximum efficiency of 89.5% and a grating capacity of 189 nuts/hr. In comparison, the I-Optimal model predicted an optimal efficiency of 85.7% and a capacity of 179 nuts/hr at 121.014 rpm, spike angle of 57°, and spike length of 12.7 mm. Frame deformation under maximum load was minimal at 0.05289 mm. The RSM-based approach effectively optimized the coconut dehusking machine, supporting the design of efficient, durable dehusking systems for agricultural applications.